KAJIAN UNSUR INTRINSIK NOVEL “PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM” KARYA DIAN PURNOMO: TINJAUAN STRUKTURAL (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and structurally analyze the intrinsic elements that constuct the novel “Perempuan yang Menangis kepada Bulan Hitam” by Dian Purnomo. The analysis covers theme, plot, characterization, setting, point of view, style of language, and moral message. The method employed is descriptive qualitative with structural approach, focusing on the interrelationship among the novel’s constituent elements. The research data consist of narrative and dialogue excerpts collected through reading and note taking techniques. The findings reveal that the novel raises a central theme of resistance against gender injustice. The conflict centers on the main character, Magi Diela, who experiences gender-based oppression as a result of the practice of kawin tangkap in Sumba. The use of a progressive plot with a strong climax, supported by contrasting social and geographical setting, effectively constructs the character’s existential dilemma. Overall, the intrinsic elements of the novel are closely interconnected, forming a complex and reflective narrative about inner conflict and Magi’s struggle against the traditional system that restrains her freedom.